National Crime Surveys: Cities Attitude Sub-Sample, 1972-1975 ([Verlag nicht ermittelbar], 1984)
This subsample of the national crime surveys consists of data on personal and household victimization for persons aged 12 and older in 26 major United States cities in the period 1972-1975. The National Crime Surveys were designed by the Bureau of Justice Statistics to meet three primary objectives: (1) to develop detailed information about the victims and consequences of crime, (2) to estimate the numbers and types of crimes not reported to police, and (3) to provide uniform measures of selected types of crimes in order to permit reliable comparisons over time and between areas. The surveys provide measures of victimization on the basis of six crimes (including attempts): rape, robbery, assault, burglary, larceny, and motor vehicle theft. The total National Crime Survey employed two distinct samples: a National Sample, and a Cities Sample. The cities sample consists of information about victimization in 26 major United States cities. The data collection was conducted by the United States Census Bureau, initial processing of the data and documentation was performed by the Data Use and Access Laboratories (DUALabs), and subsequent processing was performed by the ICPSR under grants from the Bureau of Justice Statistics (BJS). This Cities Attitude Sub-Sample study also includes information on personal attitudes and perceptions of crime and the police, the fear of crime, and the effect of this fear on behavioral patterns such as choice of shopping areas and places of entertainment. Data are provided on reasons for respondents' choice of neighborhood, and feelings about neighborhood, crime, personal safety, and the local police. Also specified are date, type, place, and nature of the incidents, injuries suffered, hospital treatment and medical expenses incurred, offender's personal profile, relationship of offender to victim, property stolen and value, items recovered and value, insurance coverage, and police report and reasons if incident was not reported to the police. Demographic items cover age, sex, marital status, race, ethnicity, education, employment, family income, and previous residence and reasons for migrating. This subsample is a one-half random sample of the Complete Sample, NATIONAL CRIME SURVEYS: CITIES, 1972-1975 (ICPSR 7658), in which an attitude questionnaire was administered. The subsample contains data from the same 26 cities that were used in the Complete Sample.